The landlocked ocean: landlocked states in BBNJ negotiations and the impact of fixed land-sea relations in global ocean governance - Sebuliba, Solomon (Frontiers in Marine Science, 2024)
This article examines the multifaceted dimensions of landlockedness within the realm of international discourse, with a particular focus on its implications for managing global commons. Drawing from socio-legal literature and auto-ethnographic experiences during the recent intergovernmental negotiations for the BBNJ agreement under the 1982 Law of the Sea (UNCLOS) as a case study, the paper prompts essential inquiries into the true essence of being landlocked in the face of global environmental challenges. Beyond traditional geographical definitions, the paper reveals the dynamic nature of landlockedness and underscores the intricate interplay of social, economic, cultural, geographical, and political factors in determining who has access to ocean space and resources and who does not. It emphasizes that landlockedness is not a static legal or physical characteristic but an ongoing process shaped by historical and political constructs. Expanding beyond the national level, the article illustrates how individuals, whether coastal or inland, experience isolation from the ocean, influencing their interactions with, perceptions of, and regulatory proposals for the ocean. This approach illuminates existing paradigms in the access, use, and management of space and resources. In conclusion, the article advocates for more inclusive and adaptable approaches in international policy debates. It calls for a departure from rigid classifications, urging for upholding collective action, recognising the intricate connections between geography, politics, law, and the environment.